2010
DOI: 10.1002/pts.919
|View full text |Cite
|
Sign up to set email alerts
|

General design of the forming collar of the vertical form, fill and seal packaging machine using the finite element method

Abstract: The basic part of the vertical form, fill and seal packaging machine is the forming collar. The forming collar provides the shape over which packaging film is smoothly formed at high speed into a cylindrical shape. Describing the forming collar geometry and hence its design is, however, remarkably difficult. This paper presents, for the first time, a flexible methodology for calculating the complete geometry of the film rather than the usually non-complete collar over which the film is formed. That is, a metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…What is obvious when viewing the sealing envelopes for the test materials and crimp design is that the maximum values are generally obtained close to, or at, the peak seal temperature and dwell time configurations. In other parts of the form–fill–seal process where variants of forming takes place, the CoF is a dominant factor. In the seal closure area, it is surmised that it is the combination of a higher CoF and bending stiffness that affects the ability of the jaws to close at lower pressures, such as that shown with PLA.…”
Section: Analysis and Discusion Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…What is obvious when viewing the sealing envelopes for the test materials and crimp design is that the maximum values are generally obtained close to, or at, the peak seal temperature and dwell time configurations. In other parts of the form–fill–seal process where variants of forming takes place, the CoF is a dominant factor. In the seal closure area, it is surmised that it is the combination of a higher CoF and bending stiffness that affects the ability of the jaws to close at lower pressures, such as that shown with PLA.…”
Section: Analysis and Discusion Of Resultsmentioning
confidence: 99%
“…As with any machine–material interaction scenario, it is important that all factors, which might serve in the sealability of the respective films, be measured and controlled. Previous studies have shown that the bending stiffness and the coefficient of friction (CoF; crimp material against film) have effects where forming and crimping take place. Hence, these were also measured and are given in Table .…”
Section: Experimental Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether there is some physical phenomena here remains an unresolved question. However, this is a second-order effect in comparison with the other effects present and does not invalidate inequality (5), which allows for possible variations in the coefficient of friction.…”
Section: Validation Of Experimental Processmentioning
confidence: 99%
“…Ideally, the material should not deform as it passes over the collar and into the tube. Most design methods are based on the (differential) geometry of the collar and tube surfaces (although a recent approach seeks to minimize deformation of the film itself and use this to obtain the collar surface). The basic shoulder geometry can be studied in terms of the intersection of conical surfaces .…”
Section: Introductionmentioning
confidence: 99%